A novel two-dimensional nickel phthalocyanine-based metal–organic framework for highly efficient water oxidation catalysis. Issue 3 (2nd January 2018) - Jia, Hongxing; Yao, Yuchuan; Zhao, Jiangtao; Gao, Yuyue; Luo, Zhenlin; Du, Pingwu
Abstract : For the first time, we report herein bottom-up fabrication of a conductive nickel phthalocyanine-based 2D MOF and use it as a highly active electrocatalyst for OER (overpotential < 250 mV) without further pyrolysis or adding conductive materials, which can facilitate the development of 2D MOFs for energy applications. Abstract : Large π-conjugated conductive two-dimensional (2D) metal–organic frameworks (MOFs) via the bottom-up approach have recently emerged as novel and interesting 2D materials. For the first time, herein we demonstrate the design and successful bottom-up fabrication of a novel noble-metal-free nickel phthalocyanine-based 2D MOF (NiPc–MOF) for highly efficient water oxidation catalysis. This NiPc–MOF can be easily grown on various substrates. The thin film deposited on FTO showed high catalytic oxygen evolution reaction (OER) activity with a very low onset potential (<1.48 V, overpotential < 0.25 V), high mass activity (883.3 A g −1 ), and excellent catalytic durability. To the best of our knowledge, this present 2D MOF film catalyst represents the best OER catalytic activity among molecular catalyst-based materials reported so far. This work represents the first synthesis of a nickel phthalocyanine-based 2D MOF material and application of the π-conjugated 2D MOF for water oxidation.